A simple sensing platform based on a 1T@2H-MoS2/cMWCNTs composite modified electrode for ultrasensitive detection of illegal Sudan I dye in food samples. Issue 5 (20th January 2022) - Wu, Qiaoling; Ji, Chun; Zhang, Lingli; Shi, Qili; Wu, Yuangen; Tao, Han
Abstract : Based on the synergistic electrocatalysis effect of 1T@2H-MoS2 nanosheets and carboxylated carbon nanotubes (cMWCNTs), a simple electrochemical sensing platform was established for the highly sensitive detection of Sudan I. Abstract : The work presented here describes a highly sensitive and simple electrochemical sensor for the detection of Sudan I dye based on a nanocomposite made of MoS2 heterogeneous nanosheets (1T@2H-MoS2 ) and carboxylated carbon nanotubes (cMWCNTs) (1T@2H-MoS2 /cMWCNTs). XPS results indicate that the content of 1T phase MoS2 was estimated to be 72% in 1T@2H-MoS2 . Electron microscopy results show that the tubular cMWCNTs are uniformly interwoven in MoS2 nanosheets to form a three-dimensional network structure. Due to the synergistic electrocatalytic ability and high electroactive surface area, the 1T@2H-MoS2 /cMWCNTs modified electrode demonstrated excellent analytical performance for Sudan I, including simple operation, good stability and a wide linear range from 5.00 × 10 −9 to 2.00 × 10 −6 mol L −1 and 2.00 × 10 −6 to 1.00 × 10 −4 mol L −1 with an ultra-low detection limit of 1.56 × 10 −9 mol L −1 . The recoveries of Sudan I from spiked real samples (chilli powder and ketchup) were in the range of 95.60% to 106.10% with low RSD (<5%), indicating that the 1T@2H-MoS2 /cMWCNTs modified electrode is a promising tool for the analysis of illegal Sudan I in food samples.